2021
DOI: 10.1016/j.cell.2021.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Selective activation of PFKL suppresses the phagocytic oxidative burst

Abstract: Highlights d Small molecules LDC7559 and NA-11 inhibit the phagocytic oxidative burst d NA-11 dampens flux through the pentose phosphate pathway to limit cellular NADPH d Cryo-EM confirms agonism of PFKL through binding at the AMP/ADP allosteric pocket d PFKL is a regulatory node for NOX2-dependent NETosis and tissue damage

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 75 publications
2
67
1
Order By: Relevance
“…While a prior report showed a requirement for GSDMD in PMA – induced NETosis 17 , we found that GSDMD had no apparent role in PMA or P. aeruginosa induced NETosis when quantified by Sytox or H3Cit and using either GSDMD-/- neutrophils or GSDMD chemical inhibitors. Further, the inhibitor used in that study (LDC7559) was found to block the oxidative burst rather than GSDMD 55 , although the difference between their findings using GSDMD mutant mice 17 and ours has yet to be determined.…”
Section: Discussioncontrasting
confidence: 52%
“…While a prior report showed a requirement for GSDMD in PMA – induced NETosis 17 , we found that GSDMD had no apparent role in PMA or P. aeruginosa induced NETosis when quantified by Sytox or H3Cit and using either GSDMD-/- neutrophils or GSDMD chemical inhibitors. Further, the inhibitor used in that study (LDC7559) was found to block the oxidative burst rather than GSDMD 55 , although the difference between their findings using GSDMD mutant mice 17 and ours has yet to be determined.…”
Section: Discussioncontrasting
confidence: 52%
“…5f,g ). Another report showed that treatment of cells with a PFK activator significantly lowered oxidative burst 40 . Activation of PFK can drain F6P.…”
Section: Resultsmentioning
confidence: 97%
“…Studies in acute oxidative stress suggest that PPP has high potential capacity to supply NADPH on demand 22 , 34 . Recent studies in various immune cells have additionally indicated the importance of PPP in immune functions 35 – 37 , including some in neutrophils suggesting the dependence of oxidative burst on glucose metabolism or oxPPP 38 40 . However, the specific metabolic reprogram that rapidly powers up neutrophil effector functions upon activation has not been quantitatively revealed.…”
Section: Mainmentioning
confidence: 99%
“…It has been reported that the stabilization of HIF-1a up-regulate the pentose phosphate pathway ensuring the cytoplasmic supply of NADPH (42)(43)(44). Furthermore, the pharmacological activation of the glycolytic pathway through the phosphofructokinase-1 liver type, as it occurs during hypoxia, inhibits NET formation (45). In sum, low oxygen tensions prompt neutrophils to cause tissue damage through a sustained degranulation and secretion of reactive oxygen species and a reduction of pro-resolving NETs.…”
Section: Discussionmentioning
confidence: 99%